Do Non-climacteric Fruits Share a Common Ripening Mechanism of Hormonal Regulation? - Fan, Dingyu; Wang, Wei; Hao, Qing; Jia, Wensuo (Frontiers in Plant Science, 2022)
Fleshy fruits have been traditionally categorized into climacteric (CL) and non-climacteric (NC) groups. CL fruits share a common ripening mechanism of hormonal regulation, i.e. the ethylene regulation, whereas whether NC fruits share a common mechanism remains controversial. Abscisic acid (ABA) has been commonly thought to be a key regulator in NC fruit ripening, however, besides ABA, many other hormones have been increasingly suggested to play crucial roles in NC fruit ripening. NC fruits vary greatly in their organ origin, constitution and structure. Development of different organs may be different in the pattern of hormonal regulation. It has been well demonstrated that the growth and development of strawberry, the model of NC fruits, is largely controlled by a hormonal communication between the achenes and receptacle, however, not all NC fruits contain achenes. Accordingly, it is particularly important to understand whether strawberry is indeed able to represent a universal mechanism for the hormonal regulation of NC fruit ripening. In this minireview, we summarized the recent research advance on the hormone regulation of NC ripening in relation to fruit organ origination, constitution and structure, whereby analyzing and discussing whether NC fruits may share a common mechanism of hormonal regulation.